Management control systems - Hartmann, Frank G. H.; Kraus, Kalle; Nilsson, Göran; Anthony, Robert Newton 1916-2006; Govindarajan, Vijay 1949- (McGraw-Hill, 2021)
"The fully updated, second edition of Management Control Systems supports students to develop an investigative approach to implementing planning and control systems for strategic success. With strong links between theory and modern real-world practices, the new edition reflects developments in global management and business, plus contemporary design and use of management control systems. Students have access to a wealth of diverse analytical cases, balanced with current content and international examples."--Publisher's description